Implementation of Continuing Professional Development for Health Professionals in Nepal - Dangal, Ganesh; Koirala, Sushil; Chapagain, Sandhya; Sharma, Shashi; Adhikari, Ramesh Kant; Shah, Ankur (Journal of Nepal Health Research Council, 2020)
Continuing Medical Education (CME) is the educational activities that serve to maintain, develop, or increase the knowledge, skills, and professional performance and relationships a physician uses to provide services for patients, the public, or the profession. Typically, Continuing Professional Development (CPD), or Continuing Physician Professional Development (CPPD) includes all activities that doctors undertake, formally and informally, including CME, in order to maintain, update, develop, and enhance their knowledge, skills, and attitudes in response to the needs of their patients.In other words, continuing professional development is any learning outside of undergraduate or postgraduate training or education that helps us maintain and improve our performance. CPD mainly encompasses self-directed and practice-based learning activities in addition to supervised education or training. CPD designates the period of education and training of doctors or health care providers commencing after completion of both basic and postgraduate medical education, thereafter extending throughout each one’s professional life.  The value and importance of CME and CPD are self-evident to every doctors and health care providers. CME-CPD actually starts early on in our career but the actual importance of CME-CPD is most relevant after specialization which may be years long in a doctor’s life. Continuing Medical Education (CME) is the educational activities that serve to maintain, develop, or increase the knowledge, skills, and professional performance and relationships a physician uses to provide services for patients, the public, or the profession. Typically, Continuing Professional Development (CPD), or Continuing Physician Professional Development (CPPD) includes all activities that doctors undertake, formally and informally, including CME, in order to maintain, update, develop, and enhance their knowledge, skills, and attitudes in response to the needs of their patients.1In other words, continuing professional development is any learning outside of undergraduate or postgraduate training or education that helps us maintain and improve our performance. CPD mainly encompasses self-directed and practice-based learning activities in addition to supervised education or training. CPD designates the period of education and training of doctors or health care providers commencing after completion of both basic and postgraduate medical education, thereafter extending throughout each one’s professional life.2 The value and importance of CME and CPD are self-evident to every doctors and health care providers. CME-CPD actually starts early on in our career but the actual importance of CME-CPD is most relevant after specialization which may be years long in a doctor’s life. Continuing Medical Education (CME) is the educational activities that serve to maintain, develop, or increase the knowledge, skills, and professional performance and relationships a physician uses to provide services for patients, the public, or the profession. Typically, Continuing Professional Development (CPD), or Continuing Physician Professional Development (CPPD) includes all activities that doctors undertake, formally and informally, including CME, in order to maintain, update, develop, and enhance their knowledge, skills, and attitudes in response to the needs of their patients.1In other words, continuing professional development is any learning outside of undergraduate or postgraduate training or education that helps us maintain and improve our performance. CPD mainly encompasses self-directed and practice-based learning activities in addition to supervised education or training. CPD designates the period of education and training of doctors or health care providers commencing after completion of both basic and postgraduate medical education, thereafter extending throughout each one’s professional life.2 The value and importance of CME and CPD are self-evident to every doctors and health care providers. CME-CPD actually starts early on in our career but the actual importance of CME-CPD is most relevant after specialization which may be years long in a doctor’s life. Continuing Medical Education (CME) is the educationalactivities that serve to maintain, develop, or increasethe knowledge, skills, and professional performance andrelationships a physician uses to provide services forpatients, the public, or the profession. Typically, Con-tinuing Professional Development (CPD), or ContinuingPhysician Professional Development (CPPD) includes allactivities that doctors undertake, formally and informal-ly, including CME, in order to maintain, update, develop,and enhance their knowledge, skills, and attitudes in re-sponse to the needs of their patients.Continuing Medical Education (CME) is the educationalactivities that serve to maintain, develop, or increasethe knowledge, skills, and professional performance andrelationships a physician uses to provide services forpatients, the public, or the profession. Typically, Con-tinuing Professional Development (CPD), or ContinuingPhysician Professional Development (CPPD) includes allactivities that doctors undertake, formally and informal-ly, including CME, in order to maintain, update, develop,and enhance their knowledge, skills, and attitudes in re-sponse to the needs of their patients.Continuing Medical Education (CME) is the educationalactivities that serve to maintain, develop, or increasethe knowledge, skills, and professional performance andrelationships a physician uses to provide services forpatients, the public, or the profession. Typically, Con-tinuing Professional Development (CPD), or ContinuingPhysician Professional Development (CPPD) includes allactivities that doctors undertake, formally and informal-ly, including CME, in order to maintain, update, develop,and enhance their knowledge, skills, and attitudes in re-sponse to the needs of their patients.